Dextran-immobilized curcumin: An efficient agent against food pathogens and cancer cells. (July 2019) - Zare, Mahboobeh; Norouzi Sarkati, Malihe; Tashakkorian, Hamed; Partovi, Razieh; Rahaiee, Somayeh
Curcumin–dextran conjugate was synthesized by free radical grafting reaction between curcumin and dextran. The chemical characterization of the conjugate was obtained by Fourier-transform infrared and 1 H-NMR (proton nuclear magnetic resonance) spectroscopy analysis, while the functionalization degree was determined by the Folin–Ciocalteu assay, finding a 22.93 mg of curcumin/g of dextran conjugate. Antioxidant activity of curcumin and curcumin–dextran conjugate was investigated employing DPPH radical method, and IC50 (the half maximal inhibitory concentration) values of curcumin and the curcumin–dextran conjugate (Cur equivalents) were 86.6 ± 0.1 and 17.4 ± 1 µM, respectively. The presence of dextran into the curcumin–dextran conjugate improved radical scavenging activities of the curcumin. In addition, antimicrobial effect of curcumin and curcumin–dextran conjugate was evaluated against gram-positive ( Listeria monocytogenes and Staphylococcus aureus ) and gram-negative ( Escherichia coli O157:H7 and Salmonella typhimurium ) bacteria. According to our experiments, gram-positive microorganisms are more sensitive to these compounds than gram-negative ones. Curcumin–dextran is a more potent bacteriostat ( S. aureus (minimum inhibitory concentration = 0.008 µg/mL), E. coli O157:H7 (minimum inhibitory concentration = 250 µg/mL), and S. typhimurium (minimum inhibitory concentration = 500 µg/mL)) and also a more potent bacteriosid against S. aureus and S. typhimurium than curcumin. The cytotoxic effects of the curcumin–dextran conjugate toward AGS, MCF-7, and normal fibroblast cell lines were determined at 48 and 72 h using an MTT assay. The results revealed the considerable antiproliferative effects of the curcumin–dextran conjugate in both AGS and MCF-7 cancer cells in comparison with fibroblast cells. This study shows that dextran as a versatile scaffold develops the biological activities of curcumin by covalent grafting and can be regarded in further bioapplications.